Affective scenes influence fear perception of individual body expressions. Issue 2 (25th October 2012) - den Stock, Jan Van; Vandenbulcke, Mathieu; Sinke, Charlotte B.A.; de Gelder, Beatrice
<x xml:space="preserve">Abstract</x> In natural viewing conditions, different stimulus categories such as people, objects, and natural scenes carry relevant affective information that is usually processed simultaneously. But these different signals may not always have the same affective meaning. Using body‐scene compound stimuli, we investigated how the brain processes fearful signals conveyed by either a body in the foreground or scenes in the background and the interaction between foreground body and background scene. The results showed that left and right extrastriate body areas (EBA) responded more to fearful than to neutral bodies. More interestingly, a threatening background scene compared to a neutral one showed increased activity in bilateral EBA and right‐posterior parahippocampal place area (PPA) and decreased activity in right retrosplenial cortex (RSC) and left‐anterior PPA. The emotional scene effect in EBA was only present when the foreground body was neutral and not when the body posture expressed fear (significant emotion‐by‐category interaction effect), consistent with behavioral ratings. The results provide evidence for emotional influence of the background scene on the processing of body expressions. Hum Brain Mapp 35:492–502, 2014. © 2012 Wiley Periodicals, Inc.